A Study Concerning the Men Handball Team UCM Reșița in the First Years of the Third Millenium - ROHOZNEANU, Dan-Mihai (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2024)
The evolution of the handball game in the last decades on international level has generated spectacular changes also at the level of club teams in Romania. A very interesting evolution was recorded by the handball team UCM Reșița, in the first years of the third millennium. This study proposes to present, analysing the reference sources for the approached topic, the way in which the men handball game developed in the town of Reșița, succeeding to obtain unique performances in Romania and Europe (wining three times in a row the Challenge Cup). Therewith, it proposes to answer the question: "Which were the factors which contributed to the team evolution towards the remarkable results obtained?"